Legal Protection Against Taxpayers After Entirement of Automatic Exchange of Information - Moh Saleh; Any Palaud (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Purpose of this study is to determine the legal consequences of the implementation of Automatic Exchange of Information related to bank secrecy and to determine the form of legal protection for taxpayers after the implementation of Automatic Exchange of Information. The author uses a normative juridical research method as well as aapproach statute and a conceptual approach. From the research results, it can be concluded that the implementation of the Automatic Exchange of Information does not completely override bank secrecy norms, but only requires financial services institutions to provide financial information for depositors and their deposits in accordance with established regulations, and the enforcement of these rules is solely for tax purposes. and not for other purposes, so that outside of taxation purposes, the regulations protecting bank secrecy are still valid. And the form of legal protection provided by the government to taxpayers is in the form of statutory regulations that still guarantee bank secrecy outside of taxation interests, that access to data opening is only given to certain officials of the Directorate General of Taxes so that confidentiality can be more guaranteed and the government will provide criminal sanctions. for officials who leak the data in accordance with the prevailing laws and regulations.